(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Urbanization is a complex social process that characterizes the growth and development of cities, as well as forms the share of urban residents in the total population. This phenomenon reflects not only demographic changes but also transformations in social systems, culture, lifestyles, and social relations. The article describes the main stages and causes of urbanization, its impact on social relations, as well as problems of urbanization such as social risks, environmental risks and instability in the urban environment. Particular attention is paid to the relationship between urbanization, globalization, technological advancements, and governance.